2020
DOI: 10.1109/jstars.2019.2955175
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Sea Ice Based on Doppler Spread Analysis of Spaceborne GNSS-R Data

Abstract: The spaceborne Global Navigation Satellite System-Reflectometry (GNSS-R) delay-Doppler map (DDM) data collected over ocean carry typical feature information about the ocean surface, which may be covered by open water, mixed water/ice, complete ice, etc. A new method based on Doppler spread analysis is proposed to remotely sense sea ice using the spaceborne GNSS-R data collected over the Northern and Southern Hemispheres. In order to extract useful information from DDM, three delay waveforms are defined and uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…Through the analysis of DDM, the two-dimensional delay waveform corresponding to different Doppler shifts were extracted to sense sea ice in [25], where the relationship between received waveforms and the theoretical waveform of a flat surface was estimated. Recent studies [25][26][27][28] indicated that sea ice can be correctly discriminated from water in up to 98.22% of cases in the monitoring of sea ice compared to collocated passive microwave data. The applications of TDS-1 data for sea ice altimetry were explored in a number of previous studies [29][30][31], while the raw data used in [29] and [30] are not in the standard dataset open to the public.…”
Section: Introductionmentioning
confidence: 99%
“…Through the analysis of DDM, the two-dimensional delay waveform corresponding to different Doppler shifts were extracted to sense sea ice in [25], where the relationship between received waveforms and the theoretical waveform of a flat surface was estimated. Recent studies [25][26][27][28] indicated that sea ice can be correctly discriminated from water in up to 98.22% of cases in the monitoring of sea ice compared to collocated passive microwave data. The applications of TDS-1 data for sea ice altimetry were explored in a number of previous studies [29][30][31], while the raw data used in [29] and [30] are not in the standard dataset open to the public.…”
Section: Introductionmentioning
confidence: 99%
“…Here and after, we directly call coherent component dominated DDM as coherent DDM, and incoherent component dominated as incoherent DDM. The whole classification idea is inspired by GNSS-R sea ice detection [17,18], and both are essentially determining the similarity to the coherent model. For the coherent DDM, it resembles the Woodward ambiguity function (WAF) without delay-doppler spreading [33], while incoherent DDM exhibits the typical "horseshoe" shape.…”
Section: Definition Of Classification Estimatormentioning
confidence: 99%
“…Although the influence of the signal incidence angle is small, the method proposed in [25] is still used in this work. The effect of the incidence angle correction is represented by the dashed lines in Figure 3 Due to the pseudorandom distribution of CYGNSS measurement, the influence of observation noise, and the spatial difference of surface roughness and vegetation cover at the specular point, currently, it is difficult to directly establish a reliable SM retrieval model at the GNSS-R specular point modeling all these factors, the optimal approach is to Due to the pseudorandom distribution of CYGNSS measurement, the influence of observation noise, and the spatial difference of surface roughness and vegetation cover at the specular point, currently, it is difficult to directly establish a reliable SM retrieval model at the GNSS-R specular point modeling all these factors, the optimal approach is to improve the SNR of reflectivity using the space-time-averaging method to form the gridded retrieval model [18]. Since the SM reference data used in this work is from the SMAP level-3 version 6 product, the individual CYGNSS reflectivity calculated with Equation ( 8) within one day will be projected into a global cylindrical 36 km × 36 km EASE-Grid 2.0 grid to align with the reference SM values, the average reflectivity is picked as the grid value.…”
Section: Soil Moisture Retrieval Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, with a large operational constellation, the GNSS-R data is ideal for flash flood remote sensing. The GNSS-R has shown a great capacity for various applications such as altimetry [26], sea surface wind [27]- [31], soil moisture (SM) [32]- [34], target detection [35], tsunami [36], [37], sea ice [38]- [43], inland water detection [44], and seasonal flood classification [45]. However, its application for flash floods detection is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%